Defining Simulation Intent. (February 2015) - Nolan, Declan C.; Tierney, Christopher M.; Armstrong, Cecil G.; Robinson, Trevor T.
Abstract: Defining Simulation Intent involves capturing high level modelling and idealisation decisions in order to create an efficient and fit-for-purpose analysis. These decisions are recorded as attributes of the decomposed design space. An approach to defining Simulation Intent is described utilising three known technologies: Cellular Modelling, the subdivision of space into volumes of simulation significance (structures, gas paths, internal and external airflows, etc.); Equivalencing, maintaining functional links between different analysis representations of the same region of design space across multiple analysis models; and Virtual Topology, which offers tools for partitioning and de-partitioning the model without disturbing the manufacturing oriented design geometry. The end result is a convenient framework to which high-level analysis attributes can be applied, and from which detailed analysis models can be generated with a high degree of controllability, repeatability and automation. There are multiple novel aspects to the approach, including its reusability, robustness to changes in model topology and the inherent links created between analysis models at different levels of fidelity and physics. By utilising Simulation Intent, CAD modelling for simulation can be fully exploited and simulation work-flows can be more readily automated, reducing many repetitive manual tasks (e.g. the definition of appropriate coupling between elements of different types and the application of boundary conditions). The approach has been implemented and tested with practical examples, and significant benefits are demonstrated. Highlights: A novel approach to capturing "Simulation Intent" is described. The design space is partitioned into cells of analysis significance. Analysis attributes are attached to these cells and their interfaces. Models are derived using Simulation Intent, design geometry and analysis attributes. By specifying a different Simulation Intent, different analysis models are obtained.